2020
DOI: 10.1111/apt.15730
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of tioguanine versus low‐dose thiopurines combined with allopurinol in inflammatory bowel disease patients

Abstract: | on behalf of the Dutch Initiative on Crohn's Colitis (ICC)This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes. SummaryBackground: Both tioguanine and low-dose thiopurines combined with allopurinol (LDTA) can be considered for the treatment of inflammatory bowel disease (IBD) when conventional thiopurines fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 40 publications
2
16
0
4
Order By: Relevance
“…Arthralgia associated with the use of thioguanine was reported with a ‘common’ (≥ 1% to < 10%) cumulative incidence in IBDREAM (1.9%; n = 11). This finding is in line with the cumulative incidence of 5.8% reported in a Dutch retrospective study ( n = 16) [ 27 ], while a Dutch prospective study reported an even higher cumulative incidence of ‘very common’, with 10.6% ( n = 10) [ 21 ]. From the latter 10 cases, seven were possibly related to arthralgia and three cases resulted in discontinuation.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Arthralgia associated with the use of thioguanine was reported with a ‘common’ (≥ 1% to < 10%) cumulative incidence in IBDREAM (1.9%; n = 11). This finding is in line with the cumulative incidence of 5.8% reported in a Dutch retrospective study ( n = 16) [ 27 ], while a Dutch prospective study reported an even higher cumulative incidence of ‘very common’, with 10.6% ( n = 10) [ 21 ]. From the latter 10 cases, seven were possibly related to arthralgia and three cases resulted in discontinuation.…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, arthralgia, pyrexia and rash associated with the use of mercaptopurine are only reported in the SmPC as part of a hypersensitivity reaction [ 12 ], and not separately. These findings were supported by recent studies [ 21 24 ] in which pyrexia, malaise, nausea and diarrhoea associated with the use of azathioprine, and arthralgia, pyrexia and rash associated with the use of mercaptopurine, were reported separately. Symptoms such as arthralgia may also be considered underlying symptoms of IBD.…”
Section: Discussionsupporting
confidence: 82%
“…Pharmacogenomics AZA is a prodrug and, after a non-enzymatic change, 88% of it is converted into mercaptopurine (MP), that can be metabolized through different pathways into another active and inactive metabolites, as shown in Figure 1 (27,28). The thiopurine methyltransferase enzyme (TPMT) methylates MP into methylmercaptopurine (MMP), an inactive metabolite associated with some adverse events, mainly hepatotoxicity.…”
Section: Using the Treatment In Selected Patients Depending On Individual Characteristicsmentioning
confidence: 99%
“…TP are cheaper compared to biologics; in fact, in some countries, before the biologics, the cost of drugs represented 25% of the IBD care cost and, after them, the cost has increased from 30 to 70% (26). Finally, the overall efficacy of TP has been demonstrated for many years and, in general, patients who respond to these drugs tend to maintain a long remission (4,27). Clinical experience with TP also helps to manage most side effects, and those that are life-threatening are uncommon.…”
Section: Introductionmentioning
confidence: 99%
“…When patients experience side-effects related to elevated 6-MMP levels, we discuss two possible strategies: to start with the combination azathioprine/allopurinol therapy or to switch to monotherapy TG. Due to the lower pill burden the latter is often preferred [20]. Also, patients who still experience mild side-effects after a rechallenge with MP can benefit from a switch to TG [21,22].…”
Section: Conventional Thiopurines and Thioguanine Therapymentioning
confidence: 99%